Increasing the calorific properties of sawdust waste from pellets by torrefaction - Lunguleasa, Aurel; Ayrilmis, Nadir; Spirchez, Cosmin; Croitoru, Catalin (BioResources, 2019)
Torrefaction, a thermal treatment, was studied as a means to increase calorific properties in sawdust biomass for some wooden species from southeast Europe. Torrefaction of wood material in the form of sawdust waste is known to modify the biomass at the chemical level, especially hemicelluloses. Four wood species, namely beech, spruce, larch, and oak, were thermally treated as sawdust waste at temperatures of 200 °C, 220 °C, 240 °C, 260 °C, 280 °C, and 300 °C for different times of 3 min, 5 min, and 10 min. The results indicated an increase in the calorific value and calorific density with increased torrefaction temperature and time. From the economic point of view, the pellets obtained from torrefied sawdust had better properties than untreated ones. The value-added pellets could compete on the market with traditional fossil fuels.
Keywords: Wooden waste; Calorific value; Sawdust; Torrefaction treatment